The Impacts of Pelvic Floor Dysfunction Counseling to Knowledge Level and Attitude of Pregnant Women with Gestational Age above Thirty Six Weeks in the Selection of Delivery Method - Surahman Hakim; Fajar Ekaputra (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine the level of knowledge about pelvic floor dysfunction before and after counseling in term pregnant women and knowing whether a difference a change of attitude in the selection method of delivery before and after counseling. Methods: This study design using pre - post test. At the beginning of our study provide some sort of written test to determine the initial knowledge of participants prior to the extension and the selection of the desired method of delivery. Having obtained the results of the test, followed by education about pelvic floor dysfunction. Then do the post-test to determine the level of knowledge of the subject and mode of delivery that would be pursued. The study took place between February and May 2016 in 5 Public Health Center (PHC) in Jakarta that PHC Warakas (North Jakarta), PHC Tanah Abang (Central Jakarta), PHC Cengkareng (West Jakarta), PHC Jatinegara (East Jakarta) and PHC Jagakarsa (South Jakarta). Results: A total of 102 study subjects who began the study gave the results of the pretest mean 71 ï‚± 10.49 (p<0.0001) and post test results of 80.725 ï‚± 7.7 (p<0.0001). Of the 102 subjects who began the study, there were two people who had previously chose method of delivery by caesarean section turned into vaginal. Conclusion: There is a change scores better in knowledge about pelvic floor dysfunction after counseling. There was no significant difference between selecting the desired method of delivery before the after counseling. [Indones J Obstet Gynecol 2017; 5-2: 99-104] Keywords: fecal incontinence, pelvic floor dysfunction, sexual dysfunction, stress urinary incontinence, uterine prolapse